2016
DOI: 10.1080/0284186x.2016.1266082
|View full text |Cite
|
Sign up to set email alerts
|

How will cancer survivors use survivorship care plans?

Abstract: Background: Survivorship care plans (SCPs) are internationally endorsed as an important tool to enhance post-treatment survivorship care. To support broad implementation of SCPs, we investigated survivors' preferences regarding SCPs. Material and methods: The study was conducted at a comprehensive cancer center. Eligible patients from 10 clinical services, generally up to 12 months following end of treatment (EOT) were approached in clinics or via telephone. A purpose-designed survey assessed survivors' intend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Another theme to emerge was the need for information, in particular advice on diet. A survey of 230 cancer survivors [22] also showed that almost all respondents (98%) desired further information following treatment, including diet and exercise. It has been pointed out that after completing medical treatment, survivors report that they are more likely to learn about cancer-specific information on their own, rather than from medical personnel [23].…”
Section: Discussionmentioning
confidence: 99%
“…Another theme to emerge was the need for information, in particular advice on diet. A survey of 230 cancer survivors [22] also showed that almost all respondents (98%) desired further information following treatment, including diet and exercise. It has been pointed out that after completing medical treatment, survivors report that they are more likely to learn about cancer-specific information on their own, rather than from medical personnel [23].…”
Section: Discussionmentioning
confidence: 99%
“…to less than 20% of a sample of patients with different cancers in a study in Australia [15] to only 11% in an American sample of brain tumour survivors [18]. This may be because the evidence behind their effectiveness remains unclear [12].…”
Section: Livestrong Tm Scp Developed In 2007) Function As a Communicmentioning
confidence: 98%
“…Elements perceived as being important by patients to incorporate into a SCP include a watch list of symptoms and signs, a treatment summary and preventative healthcare recommendations [14,15], though only half of SCPs provide all these elements and often without sufficient detail [8]. Despite recommendations from several bodies, their proposed potential benefits and a near universal desire among survivors for information in the form of a SCP [15,16], few patients report having received one [15]. Use varies from as high as 35%…”
Section: Livestrong Tm Scp Developed In 2007) Function As a Communicmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite recommendations from oncology organisations that SCP should be used, there is limited evidence that they improve long-term outcomes for cancer survivors although survivor satisfaction with the SCP is generally high. 10 …”
Section: Introductionmentioning
confidence: 99%